The Relationship between Externalities and Economic Efficiency - Marius BULEARCĂ; Cornelia NEAGU; Cristian SIMA (Communications of International Proceedings, 2020)
As announced in our previous works, this paper is part of a larger research that deals with sustainable development and environmental protection in extractive industry. In this respect, this paper is aiming to identify the relationship that may exist between externalities and economic efficiency in terms of market failure. We begin our analysis of externalities by discussing the forms that externalities can take in terms of consumption and production. Then we shall move on by explaining the links between externalities (as source of market failure) and economic efficiency. In the end, by looking at three sorts of pollution problem – a consumer-to-consumer case, a producer-to-producer case, and a case where the unintended effect is from a producer to consumers – we shall bring out all of the essential features of pollution as a market failure problem.
Keywords: Consumer; Efficiency; Externality; Market Failure; Pollution; Production Function; Producer; Property Right; Utility.